Politeness Strategies in Multicultural Interaction: A Pragmatic Study of Urban Communities - Imam Syafi'i; Musyawir Musyawir; Aswanto Aswanto (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates politeness strategies in multicultural urban communities through an empirical qualitative pragmatic design based on naturally occurring conversational data and ethnographic observation. The analysis demonstrates that urban speakers employ indirect requests, mitigated refusals, layered apologies, humor, and collective framing as adaptive facework resources in contexts marked by cultural heterogeneity and interactional uncertainty. Findings indicate that indirectness functions as pragmatic caution, enabling relational alignment without presuming shared normative expectations, while humor operates as an affiliative tool that simultaneously carries intercultural risk. Institutional environments such as workplaces, service encounters, faith-based spaces, and digital platforms further shape politeness realization by imposing hierarchical constraints and medium-specific pressures. Quantitative distributions of coded strategies confirm the centrality of mitigation and preparatory moves in high-imposition speech acts. The study advances politeness theory by emphasizing the emergence of hybrid urban norms generated through contact, mediation, and symbolic sensitivity. Methodologically, it contributes a discourse-pragmatic framework that captures politeness as a negotiated civic practice sustaining multicultural coexistence.